2023
DOI: 10.1002/anie.202305042
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Kinetic Resolution of Racemic Unactivated Alkenes via Enantio‐, Diastereo‐, and Regioselective Hydroamination

Abstract: Kinetic resolution is a powerful strategy for the isolation of enantioenriched compounds from racemic mixtures, and the development of selective catalytic processes is an active area of research. Here, we present a nickel-catalyzed kinetic resolution of racemic αsubstituted unconjugated carbonyl alkenes via the enantio-, diastereo-, and regioselective hydroamination. This protocol affords both chiral α-substituted butenamides and syn-β 2,3 -amino acid derivatives with high enantiomeric purity (up to 99 % ee) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 68 publications
(149 reference statements)
0
6
0
Order By: Relevance
“…According to the above results and literature, a plausible reaction mechanism was proposed (Figure c). The nickel­(I) hydride species I , generated from SKP-bound Ni precursor with a silane in the presence of a base, , would insert into the terminal double bond of the 1,3-diene, generating the corresponding π-allyl-Ni­(I) intermediate II .…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…According to the above results and literature, a plausible reaction mechanism was proposed (Figure c). The nickel­(I) hydride species I , generated from SKP-bound Ni precursor with a silane in the presence of a base, , would insert into the terminal double bond of the 1,3-diene, generating the corresponding π-allyl-Ni­(I) intermediate II .…”
Section: Resultsmentioning
confidence: 54%
“…Recently, metal hydride-catalyzed hydrofunctionalization of alkenes has attracted considerable attention. It has been reported that some NiH complexes demonstrate robust catalytic activity for enantioselective C–N bond-forming processes, wherein O-benzoyl hydroxylamines (BzO–NR 2 ) are used as electrophilic amination reagent which is compatible to the presence of reductant reagents in the reaction system . Accordingly, we commenced our studies on the Ni-catalyzed model reaction of phenylbutadiene 1a and morpholino benzoate 2a , and a preliminary parameter survey revealed that the reaction was best run at rt in 2-Me-THF with Ni­(COD) 2 as the Ni source in the presence of trimethoxysilane and K 2 CO 3 (for details, see SI).…”
Section: Resultsmentioning
confidence: 99%
“…The key hypothesis of this approach was the selection of a particular distinct architecture of chiral ligand (L46) bound to a nickel complex, which creates a typical chiral binding pocket that favourably recognizes one enantiomer of α-substituted alkene substrates, which led to enantioselective C-N bond construction (Scheme 42b). 73 The origin of the kinetic resolution process was confirmed by employing both (S) and (R) isomers of a model substrates for conformational analysis to envision the plausible transition state model of the migratory insertion step using DFT calculations. The favoured transition state with (S) isomer ( 52) was energetically more (1.8 kcal mol −1 ) preferable than the transition state associated with the (R) isomer (53).…”
Section: C-n Bond Formation Via Hydrofunctionalization Of Functional ...mentioning
confidence: 97%
“…In 2023, the Hong group marked a pivotal milestone in asymmetric hydroamination, employing kinetic resolution, which extracts enantioenriched compounds from racemic mixtures ( Scheme 22 ). 82 Their focus sharpened on a nickel-catalyzed kinetic resolution tailored for racemic α-substituted unconjugated carbonyl alkenes. This meticulously engineered method harmoniously combined enantioselectivity, diastereoselectivity, and regioselectivity in hydroamination.…”
Section: Advancements In Asymmetric Hydroamination and Hydroamidation...mentioning
confidence: 99%